Motivation of sport events volunteers : gender and employment status difference - Sng, Yu Xin (2016)
Despite the significant increase in number of sporting events held in Singapore, survey had shown that Singapore faces a scarcity of volunteers. Hence, to overcome this problem and recruit more volunteers, it is important for organisations to understand what motivates individuals to volunteer. The aim of the current study is to assess the determinants of motivation of sport volunteers in Singapore sporting events, and to explore the possible effect of gender and employment status difference on volunteer motivation. The study used the volunteer motivation scale to identify volunteer motivation. Online questionnaire and self-administered questionnaire were used to collect data from volunteers who are above the age of 18 and have experience in volunteering for Singapore sporting events. 87 valid responses were retained, of which there were 45 females and 42 males. 63% of the respondents were student and 31% were employed. Exploratory factor analysis extracted four factors (i.e. leisure, ego enhancement, altruistic, and external influence), and reliability coefficient of the factors ranged from .63 to .86. Independent samples t-tests showed that there were no significant differences between males and females, and between students and employed individuals in any of the extracted motivation factors, where all p-values obtained were greater than .05. Results revealed that four factors can be used to explain motivation of sport events volunteer and that volunteer motivation is similar across different gender and employment status. Results implied that organisers can adjust their marketing strategy, and recruitment message used should promote the benefits related to the four factors. Keywords: Sport event, volunteer, motivations, gender differences, employment status differences